A COMPARISON BETWEEN NOVEL AND MOVIE VERSION OF ARTHUR GOLDEN’S MEMOIRS OF A GEISHA: A STRUCTURAL ANALYSIS - ASTUTI, FITRIA WAHYU (2007)
This study deals with the similarities and differences between Memoirs of a Geisha in the novel and the movie version. This research paper is aimed at analyzing the structural elements of Memoirs of a Geisha both in the novel and movie version by finding out the similarities and differences between them. The present writer uses the theory of structural elements of novel and movie version. This research paper is conducted by using the following methods. The type of the study is comparing Arthur Golden’s Memoirs of a Geisha in the novel and the movie version. The types of data are text of the novel and movie scene. The methods of data collection are library research and observation. The technique of data analysis is descriptive qualitative research. The object of this research is Memoirs of a Geisha novel version written by Arthur Golden and the movie directed by Rob Marshall. Based on the data that have been collected and analyzed, she concludes that the similarities of both versions lie on the characters and characterization, the setting, plot, and theme. The differences lie on limitation characters and characterization, and the setting of place, plot, and point of view. Most events in the movie version are changed because Rob Marshall changes the plot of the story. He creates the movie different from the novel because he wants to make the story a little bit different from the novel but not leave the original story. He also wants to save the production costs because the story of the novel is too long, so it will need high costs if the story is not different or changed little bit from the novel. And the film also makes the audiences exhausted if the story is too long.